Syndemics of HIV with mental illness and other noncommunicable diseases: a research agenda to address the gap between syndemic theory and current research practice - Bhardwaj, Anvita (Curr Opin HIV AIDS, 2020)
PURPOSE OF REVIEW: The aim of this article is to summarize the status of syndemic research on HIV and noncommunicable diseases (NCDs) to identify opportunities for improving research to benefit prevention and treatment of NCDs among persons living with HIV. RECENT FINDINGS: The majority of research on syndemics of HIV and NCDs has been conducted in the United States, with few studies in low and middle-income countries. The substance abuse, violence, and AIDS syndemic model was used by a quarter of the studies, however, most other studies failed to outline a syndemic model for interpreting their findings. Mental illnesses were the dominant NCD (15 out of 16 studies), and only one study explored physical health NCDs. SUMMARY: Recent studies referring to syndemics of HIV and NCDs often do not meet criteria for a syndemic framework. Future research needs to assure minimum criteria are met: articulation of two or more health conditions, descriptions of social/geographic context that impact the relationship among these conditions, a syndemic model with proposed mechanisms for interaction in the particular social/geographic context, and a population or context without the observed syndemic. Expanding the current syndemic research beyond the United States context and beyond mental illness also would enrich the field.